Understanding Female Infertility: A Prospective Study on Prevalence and Associated Factors - Bairagi, Tanishka; Verma, Ankit; Nayak, S.P. Srinivas; Chakraborthy, Gunosindhu (Journal of Neonatal Surgery, 2025)
Background: Female infertility is a global health concern affecting millions of women, with causes ranging from hormonal imbalances and ovulatory disorders to structural abnormalities and lifestyle factors. Conditions like PCOS, endometriosis, and tubal blockages contribute significantly to infertility rates. Understanding its prevalence, risk factors, and treatment options is crucial for developing effective therapeutic strategies and improving reproductive health outcomes. Material & Method: This prospective study analyzed 118 young females with primary or secondary infertility to assess prevalence and contributing factors. Data were evaluated using the Chi-square test, with graphical representations. Key parameters included infertility type, BMI range, menstrual cycle regularity, bleeding duration, and correlations between diagnosis, age, and infertility type to identify patterns and risk factors. Result: This study revealed a higher prevalence of primary infertility than secondary infertility. PCOS was the most common diagnosis, followed by PCOD and ovarian cysts. Most participants had normal BMI, though many were overweight or obese. Sedentary lifestyle, weight gain, and menstrual irregularities were prominent factors influencing infertility prevalence Conclusion: The study highlights PCOS as the leading cause of infertility, with primary infertility being more prevalent. Lifestyle factors, including obesity and physical inactivity, significantly influenced reproductive health. Menstrual irregularities were also common. Early diagnosis, lifestyle modifications, and targeted interventions are crucial for improving fertility outcomes and reducing infertility-related burdens.